2017
DOI: 10.1111/nbu.12293
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D2 vs. vitamin D3: They are not one and the same

Abstract: Conflicting evidence has led to uncertainty as to whether vitamin D2 and vitamin D3 are equally efficacious in improving vitamin D status, despite historically being considered equipotent. A systematic review and meta‐analysis completed in 2012 indicated that D3 was more effective at raising vitamin D levels {using total 25‐hydroxyvitamin D [25(OH)D] as a marker of status} but the meta‐analysis identified high levels of heterogeneity between studies and a lack of statistically powered sample sizes to provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…D3, the most effective vitamin D isoform [24], can be produced in the human epidermis by solar/thermal…”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…D3, the most effective vitamin D isoform [24], can be produced in the human epidermis by solar/thermal…”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…Early studies reported conflicting results on the relative effectiveness of dietary vitamin D 3 compared with vitamin D 2 for increasing serum/plasma 25(OH)D concentrations (Tripkovic et al . ). Tripkovic et al .…”
Section: Comparative Effectiveness Of Different Forms Of Vitamin D Atmentioning
confidence: 97%
“…Vitamin D is naturally present in foods in two forms, with vitamin D 2 being present in plants and fungi whereas vitamin D 3 is found in fish, meat and eggs. There has been controversy for many years as to whether it matters if vitamin D 2 or vitamin D 3 is used as the source for raising vitamin D status (either as supplements or through food fortification) (see Tripkovic ). Results from the D 2 ‐D 3 study, which has been funded by the Biotechnology and Biological Sciences Research Council (BBSRC) – Diet and Health Research Industry Club (DRINC) programme and is the largest RCT to directly compare vitamin D 2 with vitamin D 3, has shown some exciting results in both Caucasian and South Asian populations (Wilson et al .…”
mentioning
confidence: 99%